The Analysis of Relationship Between Level of Optimism, Learning Achievement and Character of Students - Akhmad Ramli; Rivi Antoni; Arifin Arifin; Zulkifli Zulkifli; Sudadi Sudadi (Departement of Mathematics Education, 2023)
This investigation employs a quantitative approach and involves field research. The method utilized is a simple regression analysis with a total population of 50 students. The data was collected via questionnaires and documentation. The findings reveal that the students' optimism is at an excellent level, whereas their learning achievement is in the moderate range. Furthermore, there is a positive and significant correlation between optimism and academic performance. The results indicate that the f-count > f-table, and the table probability value is 0.000, which is smaller than the significance level of 0.05 (0.000 < 0.05), demonstrating a significant outcome. Thus, it can be inferred that the higher the level of optimism, the better the academic performance. The fact that optimism influences learning achievement provides opportunities to boost students' optimism. Consequently, teachers bear the responsibility of enhancing students' optimism, either directly or indirectly. By fostering and elevating an optimistic mindset in students, it is expected that they will enhance their cognitive processes and academic outcomes, paving the way for success.